Social assistance programme impacts on women's and children's diets and nutritional status - Deanna K. Olney; Aulo Gelli; Neha Kumar; Harold Alderman; Ara Go; Ahmed Raza (Wiley, 2022)
Abstract Investments in social assistance programmes (SAPs) have accelerated alongside interest in using SAPs to improve health and nutrition outcomes. However, evidence of how design features within and across programme types influence the effectiveness of SAPs for improving diet and nutrition outcomes among women and children is limited. To address this, we reviewed evaluations of cash, in‐kind and voucher programmes conducted between 2010 and 2020 among women and children, and examined associations between design features (targeting, including household and individual transfers, fortified foods and behaviour change communication) and positive impacts on diet (diet diversity, micronutrient intake) and nutrition (anthropometric indicators, haemoglobin, anaemia) outcomes. Our review has several key findings. First, SAPs improve dietary diversity and intake of micronutrient‐rich foods among women and children, as well as improve several nutrition outcomes. Second, SAPs were more likely to impact diet and nutrition outcomes among women compared with children (23/45 [51%] vs. 52/144 [36%] of outcomes measured). Third, in‐kind (all but one of which included fortified foods) compared with cash transfer programmes were more likely to significantly increase women's body mass index and children's weight‐for‐height/length Z‐score, and both women's and children's haemoglobin and anaemia. However, there is limited evidence on the effectiveness of SAPs for improving micronutrient status and preventing increased prevalence of overweight and obesity for all populations and for improving diet and nutrition outcomes among men, adolescents and the elderly. Further research in these areas is urgently needed to optimize impact of SAPs on diet and nutrition outcomes as countries increase investments in SAPs.